Program Edukasi Sebagai Upaya Peningkatan Pengetahuan Ibu Tentang Stimulasi Tumbuh Kembang Bayi: Educational Program as an Effort to Increase Mothers’ Knowledge About Infant Growth and Development Stimulation - Elvina, Ade; Maulani, Nurul; Syafitasari, Juanda; Arlenti, Lety (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Often parents do not realize when their children experience delays in growth and development. Children's development and growth will be optimal if parents are able to provide stimulation but in reality, mothers' knowledge about stimulation is still low. The purpose of community service carried out by the team in Malabero Village, Bengkulu City is to measure mothers' knowledge before and after being given health education interventions about growth and development stimulation and to provide education and demonstrations of stimulation that mothers can apply to their children. The participants who attended this activity were 30 people. This activity began with the team conducting a pre-test by distributing questionnaires to participants, then providing education and demonstrations, then evaluating the results of the intervention by distributing questionnaires back to participants for the post-test results. The results obtained were 100% of the invited participants attended with their babies and toddlers and the average difference in knowledge before and after the health education intervention on growth and development stimulation was 3.4. This activity proves that an applicable educational approach accompanied by demonstrations can increase participants' knowledge. Thus, educational and demonstration activities like this can be an important basis for the development of similar health promotion programs in other areas to support efforts to prevent delays in child growth and development and optimize growth and development from an early age. And health education about babies and toddlers should be carried out periodically in Malabero Village. Keywords: Stimulation, Growth and Development, Knowledge, Mother